Materialism as a Methodological Principle - Meškauskas, Eugenijus (Problemos, 1977)
The article reveals how materialism, as a definite conception of reality, plays the role of a universal methodological principle requiring the application of the criterion of confrontation with reality, while evaluating the contents of scientific theories. The dialectical stage of the principle requires, in addition, to take into account the concept of development in scientific investigations. From this point of view the historical change of the contents of the concepts of matter and motion of matter are analysed.